2004
DOI: 10.1073/pnas.0405702101
|View full text |Cite
|
Sign up to set email alerts
|

Resolution and evolution of the duck-billed platypus karyotype with an X 1 Y 1 X 2 Y 2 X 3 Y 3 X 4 Y 4 X 5 Y 5 male sex chromosome constitution

Abstract: The platypus (2n ‫؍‬ 52) has a complex karyotype that has been controversial over the last three decades. The presence of unpaired chromosomes and an unknown sex-determining system especially has defied attempts at conventional analysis. This article reports on the preparation of chromosome-specific probes from flow-sorted chromosomes and their application in the identification and classification of all platypus chromosomes. This work reveals that the male karyotype has 21 pairs of chromosomes and 10 unpaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 24 publications
1
93
0
1
Order By: Relevance
“…Platypuses have multiple sex chromosomes with some homology to the bird Z chromosome 16 . Males have five X and five Y chromosomes, which form a chain at meiosis and segregate into 5X and 5Y sperm 17,18 . Sex determination and sex chromosome dosage compensation remain unclear.…”
mentioning
confidence: 99%
“…Platypuses have multiple sex chromosomes with some homology to the bird Z chromosome 16 . Males have five X and five Y chromosomes, which form a chain at meiosis and segregate into 5X and 5Y sperm 17,18 . Sex determination and sex chromosome dosage compensation remain unclear.…”
mentioning
confidence: 99%
“…Neo-sex chromosome systems are known in many plants and animals, including XY 1 Y 2 in the plant Rumex acetosa (Rejó n et al, 1994), and multiple sex chromosomes due to translocations in African misteltoes (Barlow and Wiens, 1976), termites (Syren and Luykx, 1977), African pygmy mice (Veyrunes et al, 2004) and monotremes (Rens et al, 2004). As we shall describe below, the sex chromosomes of eutherian mammals represent an ancient case of neo-sex chromosomes, established after the divergence of eutherians and marsupials (Waters et al, 2001).…”
Section: What Causes Suppressed Recombination?mentioning
confidence: 99%
“…In females, five of these chromosomes are absent and the remaining five are present in duplicate. Thus, the sex chromosomes of males were described as X 1 Y 1 X 2 Y 2 X 3 Y 3 X 4 Y 4 X 5 Y 5 , and in females as X 1 X 1 X 2 X 2 X 3 X 3 X 4 X 4 X 5 X 5 (Grützner et al, 2004;Rens et al, 2004). The echidna has an equally complex sex chromosome system, and it was shown that the sex chromosomes of the platypus and echidna share homology but are not identical; the echidna has five X and four Y chromosomes, sharing seven with the platypus.…”
Section: Marsupial Sex Chromosomesmentioning
confidence: 99%